Acupuncture for Treating Attention Deficit Hyperactivity Disorder in Children: A Systematic Review and Meta-Analysis - Lin Ang; Jung Tae Kim; Kibong Kim; Hye Won Lee; Jun-Yong Choi; Eunseop Kim; Myeong Soo Lee (Medicina, 2023)
Background and Objectives: Attention-deficit hyperactivity disorder (ADHD) is a common childhood disorder characterized by inattention, hyperactivity, and impulsivity. However, it is uncertain whether the use of acupuncture (AT) in children with ADHD is supported by the current evidence. This review aims to provide updated evidence of the effectiveness of acupuncture in children with ADHD. Methods: Nine databases were searched from their inception to 28 July 2022. Two authors independently screened potentially eligible studies. The quality assessment of the selected studies was performed using Version 2 of the Cochrane risk-of-bias tool for randomized trials (RoB 2). The characteristics of the included studies were presented in a tabular form, and a meta-analysis was performed on the treatment effects of AT on ADHD symptoms. Results: Fourteen studies involving 1185 patients evaluating the efficacy of AT for ADHD treatment were included in this review. Compared to conventional medicine alone, the meta-analysis indicated that AT as an add-on to conventional medicine has a positive effect on improving conduct problems, learning problems, hyperactivity–impulsivity, and hyperactivity symptoms in ADHD patients. Similarly, AT alone was found to improve learning problems, hyperactivity–impulsivity, and hyperactivity symptoms in ADHD patients and exhibited better total treatment efficacy than conventional medicine alone. No major adverse events were reported. The risk of bias of the included studies was generally concerning. Conclusions: Evidence on the effectiveness of AT for ADHD patients is currently too limited to provide recommendations for its usage. More studies with the proper methodology are needed for the validation of AT interventions in treating children with ADHD.